Team commitment and selfesteem affecting organizational citizenship behavior (OCB) in orient overseas container line (M) sdn bhd / Razlan Nasarruddin, Nurarina Azrein and Husna Amira Mohd Taib - Nasarruddin, Razlan; Azrein, Nurarina; Mohd Taib, Husna Amira (Arshad Ayub Graduate Business School, 2019)
The transportation sector is defined by which category of companies provides services of moving goods, people and also infrastructure. Besides, the transportation industry group consists of several main industries such as marine, airlines, air freight and logistics and many others. The performance of companies in transportation industry basically is highly sensitive to organizational citizenship behavior (OCB) of employees as the demand of logistics is globally and satisfying. Therefore, the study is conducted to investigate the relationship between self-esteem and team commitment towards organizational citizenship behaviour (OCB). In this research, the concept of self-esteem, team commitment and organizational citizenship behaviour (OCB) are identified. Besides that, the scope of study covers the influences of self-esteem and team commitment towards organizational citizenship behaviour (OCB) among employees in Orient Overseas Container Line (M) SDN BHD (OOCL). The theoretical framework is proposed to see the relationship between independent variables and dependent variable. For sampling technique, a non-probability sampling is used for 105 respondents. According to findings of this research, all the independent variables showed significant relationships with organizational citizenship behavior (OCB). Among the independent variables, team commitment tends to have strongest influence on OCB. Thus, as a recommendation, OOCL should able to offer a good monetary compensation towards OOCL employees if these employees show OCB value in the organization. Finally, in order to maintain the value of OOCL services, OOCL should also consider on revising OOCL’s recent team training modules in order to increase efficiency and strengthen teamwork value of OOCL employees.